Biodegradation of Crude Oil Contaminated Soil in Kirkuk/ Iraq by using Pseudomonas Aeruginosa and Klebsiella Pneumoniae - Aqeel Mohammed Majeed Al-Ezee (Journal of Global Pharma Technology, 2018)
The aim of present study was to show crude oil biodegradation by Pseudomonas aeruginosa, K. pneumoniae. The samples of oil were obtain from tanks of crude oil belonging to Kirkuk city/Iraq. The present research was study crude oil biodegradation at a different condition (temperature and pH). The results show the, typical conditions of biodegradation, of crude oil were, temperature 37,0C and. Under typical condition, consumption level reported, P. aeruginosa and K.pneumoniae, at fourth day, (pH 7: 39.7; 37.5 and, temperature 37 0C: 43.1; 30.1 respectively). Also, cell numbers reported, P. aeruginosa and K. pneumoniae, at fourth, day (pH 7: 11.9; 11.3 X log 10 and, temperature 37 0C: 11.8; 10.4, respectively). It was, included from this study that ideal conditions of P. aeruginosa and K. pneumoniae to oil biodegradation were temperature 37 and pH 7.Keywords: Crude oil, Bio-degradation; P. aeruginosa; K. pneumoniae.